PENGARUH PEMBERIAN DAUN BANGUN – BANGUN (COLEUS AMBONICUS LOUR ) TERHADAP PRODUKSI ASI - Putri Ayu Yessy Ariescha; Ucy Tryaningsih (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2019)
Exclusive breastfeeding is very important for babies aged 0-6 months and must be given in the first hour. Exclusive breastfeeding is one of the most powerful influences on children's survival, growth and development. Despite the many benefits of breastfeeding, the coverage of exclusive breastfeeding is still low. One of the causes of mothers not giving breast milk because the milk comes out very little. So the mother gives formula milk. This study aims to determine the production of breast milk produced in mothers who were given Daun Bangun-Bangun soup and analyze the effect of giving Daun Bangun-Bangun on breast milk production in Desa Biru-Biru in Candirejo. The design of this study was quasy experimental design with a total sample of 32 people with a total sampling. 16 respondent as case group dan 16 responden as intervension group. With the type of Posttest-Only Control Design. The results of the study showed that there was a significant effect of Daun Bangun-Bangun to the production of breast milk. Significant results indicate that p = 0,000 <0,005.